Integration Of Qiyas And Maslahah Mursalah In Professional Zakat Policy Formulation In Indonesia - Muhammad Fadlurrahman; Ahmad Djalaluddin; Misbahul Munir; Said Abdelaal Abdelrahman Emam (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze how qiyas and maslahah mursalah can be integrated methodologically in the formulation of professional zakat policy in Indonesia, considering that previous studies tend to discuss the two methods separately. This study uses a descriptive qualitative approach with a library research type, where data is collected through documentation searches of official regulations, fatwas, and national and international scientific articles published from 2015 to 2026, then analyzed using content analysis techniques combined with the principles of ushul fiqh analysis. The results show that qiyas plays a role in providing technical-quantitative parameters for professional zakat such as nisab and zakat levels through analogies to gold zakat and agricultural zakat, while maslahah mursalah plays a role as a basis for legitimizing the obligation itself and directing policy adaptations in institutional aspects, digitalization, and welfare equality. These two methods complement each other and form a coherent framework of ushul fiqh argumentation, which is empirically manifested in the Fatwa of the Indonesian Ulema Council Number 3 of 2003, Law Number 23 of 2011 concerning Zakat Management, as well as various derivative policies of the National Zakat Agency.